Family outcomes of a parent-implemented early intervention for neurodevelopmental disorders: an exploratory study of family dynamics - Wong, Cecilia H. M.; Chan, Camille K. Y.; Wong, Paul W. C. (Frontiers in Public Health, 2025)
BackgroundNeurodevelopmental disorders have become global public health challenges, and early interventions have been proved to be effective in mitigating the problems and promoting the long-term functioning of people facing such challenges. These interventions had long been provided only by health professionals, but parents are now recognized for their capabilities. Parent-implemented early interventions are devised to equip parents with specialized knowledge and skills so that they can offer tailored training for their children. As these community-based interventions are designed to be implemented at home, they inevitably influence and are influenced by the family systems. While the family dynamics play a key role in determining the efficacy of the intervention, still little is known about the familial factors, as the focus on the existing literature is on the changes of the parent–child dyads. This research bridged this knowledge gap in implementation sciences by investigating how the family members who did not partake in the training reacted to the parent-implemented interventions (PIIs) at home.MethodsA qualitative study was conducted between August 2023 and July 2024 in Hong Kong, examining the impacts of a localized version of the World Health Organization Caregiver Skills Training. In total, 22 respondents participated in five focus group discussions. Inductive reflexive thematic analysis was applied to construct codes, themes, and frameworks.ResultsFour levels of responses—Level 0: Reject, Level 1: Support, Level 2: Attempt, and Level 3: Embrace—were identified, and these themes were on a continuum of families’ involvement in the practice of PII. Factors that promoted or discouraged their involvement were discussed. Evidence has confirmed that PII had indirect impacts on family dynamics, and the responses of family members affected the intervention effectiveness and the mental health of the caregiver-participants.ConclusionThis research responded to the call to improve public health evaluations. It moved beyond the linear changing processes in the intervention design, addressed the complexity of the social systems, and explicated the multidimensional changing processes in a family—the immediate context where parent-implemented early intervention was implemented. It contributed to build initial frameworks on the familial influences and support the future development of the intervention and research designs.